Essential plant nutrients : uptake, use efficiency, and management - Naeem, M.; Ansari, Abid A.; Gill, Sarvajeet Singh (Springer International Publishing, 2017)
This book explores the agricultural, commercial, and ecological future of plants in relation to mineral nutrition. It covers various topics regarding the role and importance of mineral nutrition in plants including essentiality, availability, applications, as well as their management and control strategies. Plants and plant products are increasingly important sources for the production of energy, biofuels, and biopolymers in order to replace the use of fossil fuels. The maximum genetic potential of plants can be realized successfully with a balanced mineral nutrients supply. This book explores efficient nutrient management strategies that tackle the over and under use of nutrients, check different kinds of losses from the system, and improve use efficiency of the plants. Applied and basic aspects of ecophysiology, biochemistry, and biotechnology have been adequately incorporated including pharmaceuticals and nutraceuticals, agronomical, breeding and plant protection parameters, propagation and nutrients managements. This book will serve not only as an excellent reference material but also as a practical guide for readers, cultivators, students, botanists, entrepreneurs, and farmers.
5.4.2 Agronomic Efficiency (AE).
Keywords: Plants -- Nutrition.; Plant nutrients.; elektronické knihy; electronic books